The Effectiveness of Baby Massages Using Audiovisual Approach for Improving Interactions between Mother and Infant in Kradenan, Srimulyo, Piyungan, Bantul - Widyaningrum, Rahmah (Journal Of Nursing Practice, 2018)
Background: the golden period of time (0-12 months) is a critical period for infant that require good stimulation to reach normal physiological development. Baby massage is one stimulation method that was given by parents to enhance the bonding between mothers and their babies. Audio-visual technique is one of the best method to deliver information for mother to perform self-baby massage at home, further increasing attachment between them.Purpose: to evaluatethe effectiveness of baby massages using audiovisual approach for improving interactions between mother and infant in Kradenan, Srimulyo, Piyungan, Bantul. Methods: This was a quasi experimental design with pretest-posttest. Study was conducted from August to September 2017 using total subjects of 20 pairs of mothers and babies. The inclusion criteria were normal birthweight, 38-42 weeks gestation age, APGAR score>7, breastfed, and didn’t have contraindication with massage procedure. Sample was divided into two groups; treatment group (audio-visual delivery) and control group (leaflet delivery). Ten subjects for treatment group were purposively recruited from Posyandu Pantang Mundur, Kradenan whereas the others were similarly recruited from Posyandu Monggang. Data was presented as frequency distribution and analyzed using independent sample t-test. Results: There was no difference between maternal and infant interactions at the beginning of the study (p = 0.16). After two weeks treatment, there is no significance difference between treatment and control group (p=0.42).Mother and Infant bonding scorewas increased in treatment group although not significantly different (p=0.21). Conclusion: Baby massage can improve bonding between mother and baby. Further study is required to asses the effectiveness of baby massage on attachment between mother and baby.